Response to "Do Radical-Right Parties Use Descriptive Representation Strategically? A Replication of Weeks et al. (2023)" - Ana Catalano Weeks; Bonnie M. Meguid; Miki Caul Kittilson; Hilde Coffé (Institute for Replication (I4R), 2024)
Guinaudeau and Jankowski reassess our recent study on the use of strategic descriptive representation among political parties in Europe. The authors successfully replicate the vast majority of our findings and perform a number of additional robustness checks. They claim that one of our key findings is sensitive to the inclusion of one observation (the Front National, FN, 2012), and that alternative measurement or modeling strategies return different results. In this response, we address each claim in turn. We apply influential case diagnostics to detect all influential cases in our multilevel models, so as not to arbitrarily delete one influential observation but not another. On removing all influential cases, our results remain substantially the same. More importantly, because we do not agree with arbitrarily dropping observations, our findings are robust to different handling techniques for influential cases in multilevel models which downweight influential cases. Further, and in line with our original mixed methods approach, we provide an additional influential case study of the use of strategic descriptive representation by the FN in 2012, which is supportive of our theory and quantitative evidence. Finally, we respond to questions about our measurement and modeling decisions by highlighting the theoretical framework and scholarly literature that informs these decisions, which is largely disregarded by GJ.
Keywords: 330